Floristic and structural variations in Cerrado fragment after three years of evaluation - Silva, Patrícia Oliveira da; Menino, Gisele Cristina de Oliveira; Silva, Laísa Cristine dos Santos; Dourado, Daiane Moreira; Ribeiro, Suzanne da Costa; Oliveira, Thais Cristina Sousa de (Revista Ecologia e Nutrição Florestal - ENFLO, 2019)
Temporal monitoring of plant biodiversity is increasingly needed. In view of the above, this study sought to evaluate if there are floristic and structural changes in “Cerradão” fragment, Rio Verde city, Goiás state, Brazil, in a time span of three years. Two inventories were carried out: the first one was carried out in 2011, where 20 plots of 100 m² each were established; the second inventory was performed in 2014, where all individuals from the first inventory were remediated and those who met the minimum inclusion criteria were recorded. The changes were evaluated by comparisons between: basal area, families, genera and species, number of individuals, density, dominance, frequency, importance value, Pielou equability and Shannon diversity. There were few changes, and statistically, there was no difference between inventories. The family Calophyllaceae and included Burseraceae were excluded. Six genera were excluded and three were excluded. In 2011, 64 were inventoried, while in 2014 there were 61 species. The recruits numbered 43, while the number of individuals killed was 81. Thus, the total number of individuals sampled in the first inventory (n = 394) was higher than the second (n = 356). To detect changes in the species recruitment and mortality in this ecosystem, it is recommended that the monitoring period be extended, with a larger number of inventories.